Composite materials as a source of energy resources economy in building - Serdyuk, V.; Franyshina, S. (Ways to Improve Construction Efficiency, 2019)
In this article the main directions of reduce energy intensity (embodied energy) in building materials are discussed. Also, the total characteristics and perspective way to use composite materials in building production are represented. The authors have been analyzed the experimental features of the composite material (construction fittings). The modern world tendencies production and consumption of composite construction fittings are presented.